Prenatal care and obstetric psychoprophilaxis in pregnant women of primary healthcare of a district of Callao: Atención prenatal y psicoprofilaxis obstétrica en gestantes del primer nivel de un distrito del Callao - Basilio_Rojas, Marlene Raquel (2020)
Objective: To determine the frequency of prenatal care (PNC) and obstetric psychoprophylaxis (OP) sessions in pregnant women who come to the Mi Perú Health Center, in the Mi Perú district, Callao Region. Materials and methods: Cross-sectional descriptive study. The population was made up of pregnant women attended at the Mi Perú Health Center during 2019. The sample was census including 278 pregnant women, 10 were discarded due to incomplete data. The instrument used was a questionnaire made up of sociodemographic characteristics, maternal characteristics, and prenatal and postnatal care. Results: The analysis was performed with 268 pregnant women with a mean age of 25.55 years (SD = 6.29; Range: 14 to 46), 66.8% (n = 179) had six or more PNCs and 51.5% (n = 138) were captured in the first trimester of pregnancy. The highest proportion of controlled pregnant women were living with or married (p = 0.031). The pregnant women who had less than two children mostly complied with having at least six NPC (p = 0.049). The pregnant women who had six or more PNC participated in more psychoprophylaxis sessions (p <0.001). The greatest number of pregnant women with six or more PNCs were captured in the first trimester of pregnancy (p <0.001). Conclusions: Pregnant women with at least 6 PNC are mostly cohabiting or married, have fewer than two children, participated in a greater number of OP sessions and were captured in the first trimester of pregnancy. Keywords: Prenatal Care; Prenatal Education, Primary Health Care; Peru (Source: MeSH, NLM).